Cattle pathogen tritrichomonas foetus (Riedmüller, 1928) and pig commensal Tritrichomonas suis (Gruby & Delafond, 1843) belong to the same species - Tachezy, Jan; Tachezy, Ruth; Hampl, Vladimír; Sedinová, Miroslava; Vanacová, Stepánka; Vrlík, Martin; Van Ranst, Marc; Flegr, Jaroslav; Kuldaa, Jaroslav (The Journal of eukaryotic microbiology, 2002)
A number of reports suggest that the sexually transmitted pathogen of cattle, Tritrichomonasfoetus, and a gastrointestinal commensal of pigs, Tritrichomonas suis, are very similar and may be co-specific. A conclusive review of the taxonomic and nomenclatural status of these species has not been presented so far. Toward this end, we reexamined and compared porcine and bovine trichomonads with regard to their morphology, pathogenic potential, and DNA polymorphism. Using light and electron microscopy, no distinguishing features between T. foetus and T. suis strains were found in size, general morphology, and karyomastigont structure. Both bovine and porcine trichomonads showed pathogenic potential in the subcutaneous mouse assays and did not separate into distinct groups according to strain virulence. Three DNA fingerprinting methods (i.e. RFLP, RAPD, and PCR-based analysis of variable-length DNA repeats) that produce species-specific DNA fragment patterns did not distinguish between the bovine and porcine strains. Sequencing of a variable 502-bp DNA fragment as well as comparison of 16S rRNA gene sequences did not reveal species-specific differences between the cattle and porcine strains. Therefore, we conclude that T. foetus and T. suis belong to the same species. To prevent confusion that may arise from T. foetus-T. suis synonymy, we propose to suppress the older name suis and maintain its accustomed junior synonym foetus as a nomen protectum for both cattle and porcine trichomonads. The case has been submitted to the International Commission on Zoological Nomenclature for ruling under its plenary power.
Keywords: Molecular Sequence Data; RNA, Ribosomal, 16S; DNA fingerprinting; DNA Fingerprinting; technika náhodné amplifikace polymorfní DNA; skot; protozoální infekce; protozoální infekce zvířat; Swine Diseases; Protozoan Infections, Animal; protozoální DNA; nemoci prasat; Swine; Tritrichomonas foetus; nemoci skotu; RNA ribozomální 16S; zvířata; Random Amplified Polymorphic DNA Technique; fylogeneze; Cattle; Protozoan Infections; Cattle Diseases; prasata; molekulární sekvence - údaje; DNA, Protozoan; Phylogeny; Animals